SAT0579 AN ELECTRONIC MDHAQ (MULTIDIMENSIONAL HEALTH ASSESSMENT QUESTIONNAIRE) GIVES SIMILAR RESULTS TO A PAPER VERSION. (June 2019) - Riad, Mariam; Obreja, Elena; Castrejon, Isabel; Pincus, Theodore
Abstract : Background: A self-report multi-dimensional health assessment questionnaire (MDHAQ) is used in many routine care rheumatology settings as a pragmatic tool to recognize efficacy and adverse events. The MDHAQ is informative in all rheumatic diseases in which it has been studied. An electronic version of the MDHAQ (eMDHAQ) could offer several advantages, including completion at home rather than in the waiting area and completion from any site between visits to report possible change in status and/or adverse events of a medication. Furthermore, the 4-page, "new patient" eMDHAQ can allow a patient to store a full medical history at a password-protected, secure website. Reports of the patient history can be available for an electronic medical record (EMR) without dictation or typing by the doctor, although interaction with the EMR vendor is required, which often has proven difficult. Implementation of eMDHAQ software requires documentation that eMDHAQ responses are similar to those on a paper MDHAQ. Objectives: To compare scores on an eMDHAQ vs paper version of MDHAQ. Methods: All patients with all diagnoses complete a paper MDHAQ at all visits in the waiting area as part of routine clinical care in one setting. Consecutive patients completed MDHAQ in paper and in an iPad at the same visit. The MDHAQ includes 0-10 scores for physical function, pain and patient global visual analog scales (VAS), compiled into 0-30 RAPID3, as well as a 0–48 self-report painful joint count, and 0–60 symptom checklist. For this study, at the conclusion of the visit, the rheumatologist asked a patient if she/he would volunteer to complete an eMDHAQ on an iPad indicating no problem if a patient declined for any reason. Patients who agreed to participate completed the an eMDHAQ, with identical content to the paper MDHAQ. The patient also completed a 3-query questionnaire, with 2 VAS concerning the value of the MDHAQ to the patient or the doctor (0= no value, 10= great value), and a query of her/his preference for the eMDHAQ vs paper MDHAQ or no preference. Test-retest reliability was examined by intraclass correlation coefficients (ICC). Results: 65 patients completed the study. The ICC for physical function, patient global VAS, and RAPID3 was >0.9 indicating excellent reliability between the electronic and paper versions, while the ICC for pain, self-report painful joint count, and symptom checklist was ≥0.75, indicating good reliability. Differences between the 2 versions were within variation on the paper questionnaire. The mean rating for the value of MDHAQ was 8.85/10 to the patient, and 8.88/10 to the doctor. Among the 65 patients, 43 (66%) indicated a preference for the eMDHAQ, 7 (11%) for the paper MDHAQ, and 15 (23%) indicated no preference. Conclusion: An eMDHAQ appears to have similar performance compared to a paper MDHAQ version. A high percentage of patients prefer the digital version to paper, although about 20% of patients are likely to require a paper MDHAQ. An eMDHAQ offers remote completion at home, before and/or between visits, to report issues concerning efficacy and/or adverse events. Expanded eMDHAQ software can allow a doctor to develop flowsheets and a database for all patients, a full patient medical history, and interfacing with any electronic medical record (EMR), although that requires interaction with the EMR vendor, which often is difficult. The eMDHAQ appears useful independent of the EMR. Disclosure of Interests: None declared